2013
DOI: 10.1038/jcbfm.2013.80
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Lesions on Functional Networks after Stroke

Abstract: While ischemic stroke reflects focal damage determined by the affected vascular territory, clinical symptoms are often more complex and may be better explained by additional indirect effects of the focal lesion. Assumed to be structurally underpinned by anatomical connections, supporting evidence has been found using alterations in the functional connectivity of resting-state functional magnetic resonance imaging (fMRI) data in both sensorimotor and attention networks. To assess the generalizability of this ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 51 publications
9
66
0
Order By: Relevance
“…Symptom severity correlated with decreased connectivity, and recovery from symptoms correlated with the recovery of normal connectivity patterns. Similar results have been reported regarding the sensorimotor [Carter et al, 2010; Carter et al, 2012; Golestani et al, 2013; Grefkes et al, 2008; Ovadia-Caro et al, 2013; Park et al, 2011; Wang et al, 2010] and language networks [Warren et al, 2009]. DMN disruption has been commonly observed by resting-state functional studies in patients with mild cognitive impairment [Sorg et al, 2007; Wang et al, 2006] vascular cognitive impairment with subcortical lesions [Sun et al, 2011], patients with carotid stenosis [Cheng et al, 2012; Lin et al, 2014] Regarding the role of the DMN on cognitive performance in stroke patients, we know only of one recent study [Tuladhar et al, 2013] carried out.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Symptom severity correlated with decreased connectivity, and recovery from symptoms correlated with the recovery of normal connectivity patterns. Similar results have been reported regarding the sensorimotor [Carter et al, 2010; Carter et al, 2012; Golestani et al, 2013; Grefkes et al, 2008; Ovadia-Caro et al, 2013; Park et al, 2011; Wang et al, 2010] and language networks [Warren et al, 2009]. DMN disruption has been commonly observed by resting-state functional studies in patients with mild cognitive impairment [Sorg et al, 2007; Wang et al, 2006] vascular cognitive impairment with subcortical lesions [Sun et al, 2011], patients with carotid stenosis [Cheng et al, 2012; Lin et al, 2014] Regarding the role of the DMN on cognitive performance in stroke patients, we know only of one recent study [Tuladhar et al, 2013] carried out.…”
Section: Discussionsupporting
confidence: 82%
“…Previous works showed that localized brain lesions can cause connectivity-based changes in regions that are structurally intact and far from the lesion site [Carter et al, 2010; Carter et al, 2012; Crofts et al, 2011; Dacosta-Aguayo et al, 2014a,b; Golestani et al, 2013; Grefkes et al, 2008; He et al, 2007; Nomura et al, 2010; Ovadia-Caro et al, 2013; Park et al, 2011; Tuladhar et al, 2013; Warren et al, 2009]. The relationship between alterations in functional connectivity after stroke and behavioral outcome/performance has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Excitingly, more recent tools like advanced structural imaging, diffusion tensor imaging (DTI), diffusion spectrum imaging (DSI) and computational network modeling can be used to tell us which brain regions are the best candidates for compensation by characterizing their connectivity and network properties, respectively (Dijkhuizen et al, 2012; Ovadia-Caro et al, 2013). Moreover, a recent study by Cipollari and colleagues demonstrated that, in the post-stroke aphasic population, tDCS can be paired with TMS-EEG to target and modulate specific areas of excitability, resulting in specific language improvements (Cipollari et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, with conventional task-based MRI, researchers are limited by the requirement to select the appropriate behavioral assay. In a recent study illustrating this benefit, Ovadia-Caro et al (2013) sought to evaluate whether iFC within networks that included the injured area following stroke were more affected and for longer durations than iFC in networks that did not include the injured area. R-fMRI data were collected from 31 stroke patients with heterogeneous lesions.…”
Section: Structure-function Relationships and The Brain’s Response Tomentioning
confidence: 99%